The Effect of Auditor Competence, Independence, And Experience on Audit Quality in Public Accounting Firm (KAP) in Bali Province - HENDRAWAN, I Made Toni Hendrawan; SANJAYA, I Gusti Ngurah; YUDHA, Cokorda Krisna (Journal of Governance, Taxation and Auditing, 2024)
The purpose of this study is to determine the influence of auditor competence, independence, and experience on audit quality. This research was conducted at a Public Accounting Firm located in the Province of Bali. The population used in this study is all auditors who work in several Public Accounting Firms in Bali Province. The sampling method in this study is by using convenience sampling, which is as many as 80 respondents. The data collection method used in this study is in the form of a questionnaire. Data analysis technique using Partial Least Squares. The results of this study show that auditor competence has a significant positive effect on audit quality, auditor independence has a significant positive effect on audit quality and auditor experience has a significant positive effect on audit quality. It is hoped that the Public Accounting Firm in Bali Province, can direct auditors to take part in training programs or certification of the public accounting profession, can provide regular training that focuses on the implementation of independence and provide mentoring programs for senior auditors or KAP partners as mentors for junior auditors, so that they can learn from direct experience.